PEMBELAJARAN ESTETIKA WACANA TUTUR UPACARA PENGANTIN JAWA - Suwarna Suwarna (LPMPP Universitas Negeri Yogyakarta, 2008)
AbstractThe aesthetic aspect in the Javanese wedding ceremony spoken discourse isvery important and even it can take the place of the semantic aspect. Speakersemphasize more on the former than on the latter. This is the uniqueness of theJavanese wedding ceremony spoken discourse. Such a phenomenon sometimesresults in a controversy between practitioners in the Javanese wedding ceremonyand the audience. This study on the aesthetic aspect in the Javanese weddingceremony spoken discourse was supported by empirical and reflective data. Theanalysis units included sounds, words, phrases, clauses, and sentences. On thebasis of the analysis, it can be concluded that (1) the aesthetic aspect of the Javanesewedding ceremony spoken discourse comprises the phraseology, figures ofspeech, idioms, and aesthetic diction; and ( 2)it shows a communication register.Keywords: aesthetic aspect, Javanese wedding ceremony spoken discourse,empirical and reflective data